Acute heart failure presentations and outcomes during the fasting month of Ramadan: an observational report from seven Middle Eastern countries. (1st February 2018) - Salam, Amar M.; Sulaiman, Kadhim; Alsheikh-Ali, Alawi A.; Singh, Rajvir; Asaad, Nidal; Al-Qahtani, Awad; Salim, Imtiaz; AlHabib, Khalid F; Al-Zakwani, Ibrahim; Al-Jarallah, Mohammed; AlMahmeed, Wael; Bulbanat, Bassam; et al.
Abstract: Background: Fasting during the month of Ramadan is practiced by over 1.5 billion Muslims worldwide. It remains unclear, however, how this change in lifestyle affects heart failure, a condition that has reached epidemic dimensions. This study examined the effects of fasting in patients with acute heart failure (AHF) using data from a large multi-center heart failure registry. Methods and results: Data were derived from Gulf CARE (Gulf aCute heArt failuRe rEgistry), a prospective multi-center study of consecutive patients hospitalized with AHF during February–November 2012. The study included 4, 157 patients, of which 306 (7.4%) were hospitalized with AHF in the fasting month of Ramadan, while 3, 851 patients (92.6%) were hospitalized in other days. Clinical characteristics, precipitating factors, management, and outcome were compared among the two groups. Patients admitted during Ramadan had significantly lower prevalence of symptoms and signs of volume overload compared to patients hospitalized in other months. Atrial arrhythmias were significantly less frequent and cholesterol levels were significantly lower in Ramadan. Hospitalization in Ramadan was not independently associated with increased immediate or 1-year mortality. Conclusions: The current study represents the largest evaluation of the effects of fasting on AHF. It reports an improved volume status in fasting patients. There were also favorable effects on atrial arrhythmia and total cholesterol and no effects on immediate or long-term outcomes.